The Effects of Lucky Draw Sales Promotion on Brand Loyalty in Mobile Telecommunication Industry - Asiamah, E.; Quaye, D.; Nimako, S. (Emerald Publishing Limited, 2016)
Purpose – The purpose of this paper is to empirically examine the relationship between lucky draw sales promotion (LDSP) and the four phases of brand loyalty in the telecommunication industry. Design/methodology/approach – A self-administered structure questionnaire was used to collect primary data from conveniently sampled 338 lucky draw winners in the Ghanaian telecommunication industry. A response rate of 67.1 percent was obtained for data analysis using structural equation modeling approach. Findings – It was found that LDSP positively relate to cognitive brand loyalty, and to behavioral brand loyalty through affective and conative brand loyalty. All hypothesized relationships among the sequential four-stage loyalty were confirmed, except the direct relationship between LDSP and behavioral brand loyalty. Research limitations/implications – The findings are limited to lucky draw winners in the telecommunication industry. Practical implications – Marketers can increase brand loyalty and profit more from their customers through targeted programs with hedonic benefits to build strong commitment level (conative brand loyalty), strong favoritism (affective brand loyalty) and strong beliefs about the superiority (cognitive brand loyalty) of a brand. Originality/value – Theoretically, this study fills the void of empirical studies on non-price sales promotion techniques of lucky draw and customer brand loyalty in the telecommunication sector in developing economy context, and contributes to the body of knowledge in the area of customer brand loyalty and LDSP.
Keywords: Ghana; Brand loyalty; Lucky draw; Sales promotion; Telecommunication industry